Interface PCI para PC compatible - Micolini, Orlando (2007)
We call BUS to any group of lines whose main purpose its interconnect different devices. One of the most critical problem in digital aplicattions its to establish a fast access communication between peripheral devices. With the intention of diminishing the limitations in the data transfer rate, in year 1992, Intel develops the Standard bus of interconnection of peripheral components (PCI). The PCI Bus, is the most used standard for the development of aplication where work togheter external components to the CPU; this paper discuss the development of my end career project, which raises the implementation of a CORE, intrument that allows to fulfill the highest requirements of the communication protocol PCI, this instrument is implemented on a reprogrammable logic FPGA Board. Also, explain the implement of drivers for testing the development under an operating system, and several visual aplications were created to validate the communication and bidirectional data transfer. At the end of this paper, we measured and studied the results to specify the reasons that allows us to affirm that the development is successful.